Corporate Social Responsibility in Nepalese Commercial Bank with reference to Bank of Kathmandu Limited - Kandel, Laxman Raj (NCC Journal, 2018)
Corporate social responsibility (CSR) is all about companies managing their business process to produce the overall positive impact on the society. The interest for CSR has grown rapidly the recent years and people started to demand corporate social responsibility from the company. CSR is connected with corporate behaving ethically, morally and socially responsible towards the society. This research focuses on investigating why companies engage in CSR, how they apply CSR and how CSR can affect financial performance. It was found that the employees and the people in general do get motivated by their organization. All the respondents were very positive and energized about being part of the CSR activities provided with the opportunities. BOK Ltd has focused their CSR activities related with the health, education and environment with the name as BOK health, BOK education and BOK environment initiation. BOK has tried to cover the different aspect of essential factors in anyone’s life. Majority of the respondents’ views that CSR activities has the positive relation and can contribute on the financial performance of the company as it increases the good image and goodwill of the organization. CSR needs planning and proper implementation so that the society could actually have positive impact from CSR activities.In Nepalese context the organization do not emphasize in CSR activities rather they give priorities to earn more profit and flourish their business. NCC Journal Vol. 3, No. 1, 2018, page: 90-99